2014
DOI: 10.1177/0959683614540961
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructions of deltaic environments from Holocene palynological records in the Volga delta, northern Caspian Sea

Abstract: New palynological and ostracod data are presented from the Holocene Volga delta, obtained from short cores and surface samples collected in the Damchik region, near Astrakhan, Russian Federation in the northern Caspian Sea. Four phases of delta deposition are recognized and constrained by accelerated mass spectrometry (AMS) radiocarbon ages. Palynological records show that erosive channels, dunes (Baer hills) and inter-dune lakes were present during the period 11,500-8900 cal. BP at the time of the Mangyshlak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…BP, Fig. 6), followed by the Derbent lowstand period (Kroonenberg et al, 2007(Kroonenberg et al, , 2008Richards et al, 2014), and the 'Medieval Warm Period' (with development of pine forest cover, Fig. 11.…”
Section: Discussionmentioning
confidence: 96%
“…BP, Fig. 6), followed by the Derbent lowstand period (Kroonenberg et al, 2007(Kroonenberg et al, , 2008Richards et al, 2014), and the 'Medieval Warm Period' (with development of pine forest cover, Fig. 11.…”
Section: Discussionmentioning
confidence: 96%
“…, ); and (vii) the northern Caspian Sea (Richards et al. ). The irregular height of the septa, the occurrence of a high septum at the junction of the paraplate 1′′′′ and the sulcus, and the low intratabular relief separate I. caspienense from all other extant Impagidinium species (Marret et al.…”
mentioning
confidence: 99%
“…(v) Holocene of the Caspian Sea (Leroy et al 2007(Leroy et al , 2013a; (vi) the late Pleistocene to Holocene of the centre of the middle and south Caspian Sea basins (Leroy et al 2013b; and (vii) the northern Caspian Sea (Richards et al 2014). The irregular height of the septa, the occurrence of a high septum at the junction of the paraplate 1 0000 and the sulcus, and the low intratabular relief separate I. caspienense from all other extant Impagidinium species (Marret et al 2004, p. 13).…”
mentioning
confidence: 99%
“…Overlying sediments of the Kirmaky Suite are dated as early Pliocene (Zanclean) based on magnetostratigraphy (van Baak 2015) and these fluvio-lacustrine beds contain occasional Spiniferites cruciformis, in association with Caspidinium rugosum Marret in Marret et al 2004 and varied numbers of freshwater algae (Richards 2012). Spiniferites cruciformis is then rare but consistently present within the sediments of the Pliocene Productive Series (Richards et al 2014a) and becomes locally abundant during the Pleistocene (Richards et al 2011(Richards et al , 2014a and new data shown in Sect. 3).…”
Section: Spiniferites Cruciformismentioning
confidence: 65%